The evolutionary origin and population history of the grauer gorilla. (25th January 2016) - Tocheri, Matthew W.; Dommain, René; McFarlin, Shannon C.; Burnett, Scott E.; Troy Case, D.; Orr, Caley M.; Roach, Neil T.; Villmoare, Brian; Eriksen, Amandine B.; Kalthoff, Daniela C.; Senck, Sascha; Assefa, Zelalem; et al.
ABSTRACT: Gorillas living in western central Africa ( Gorilla gorilla ) are morphologically and genetically distinguishable from those living in eastern central Africa ( Gorilla beringei ). Genomic analyses show eastern gorillas experienced a significant reduction in population size during the Pleistocene subsequent to geographical isolation from their western counterparts. However, how these results relate more specifically to the recent biogeographical and evolutionary history of eastern gorillas remains poorly understood. Here we show that two rare morphological traits are present in the hands and feet of both eastern gorilla subspecies at strikingly high frequencies (>60% in G. b. graueri ; ∼28% in G. b. beringei ) in comparison with western gorillas (<1%). The intrageneric distribution of these rare traits suggests that they became common among eastern gorillas after diverging from their western relatives during the early to middle Pleistocene. The extremely high frequencies observed among grauer gorillas—which currently occupy a geographic range more than ten times the size of that of mountain gorillas—imply that grauers originated relatively recently from a small founding population of eastern gorillas. Current paleoenvironmental, geological, and biogeographical evidence supports the hypothesis that a small group of eastern gorillas likely dispersed westward from the Virungas into present‐day grauer range in the highlands just north of Lake Kivu, either immediately before or directly after the Younger Dryas interval. We propose that as the lowland forests of central Africa expanded rapidly during the early Holocene, they became connected with the expanding highland forests along the Albertine Rift and enabled the descendants of this small group to widely disperse. The descendant populations significantly expanded their geographic range and population numbers relative to the gorillas of the Virunga Mountains and the Bwindi‐Impenetrable Forest, ultimately resulting in the grauer gorilla subspecies recognized today. This founder‐effect hypothesis offers some optimism for modern conservation efforts to save critically endangered eastern gorillas from extinction. Am J Phys Anthropol 159:S4–S18, 2016. © 2016 Wiley Periodicals, Inc.